Wayang dan Mutasi Value of Islam Dalam Permainan Wayang - Ahmad Fauzi Imron (Institut Ilmu Keislaman Zainul Hasan Genggong, 2016)
Islam is a religion rahmatan lil ‘Alamin (blessing for theuniverse), of course, we as Muslims are required to make Islam asguidance in social life, because sometimes the habits or norms terben tukin society are not in accordance with the teachings of Islam we alreadybelieve to be true. For that it is necessary the straightening straighteningmengkiblat in the teachings of Islam, which indeed it is an absolutething to do as a Muslim, which of course it can not be separated fromthe translation of translation as a form of extracting the values ofIslam to understand. The rest leave in case there is need for appropriatemethods as the approach used in the hang of the moral values of Islamto the community.In this study the researchers wanted to know the purpose of establishinga puppet in the hamlet syadat Gentong as media approach to disseminatethe teachings of Islam and the effectiveness of the puppet syadat intransforming the teachings of Islam to the people hamlet Gentong. Thisresearch was conducted in the hamlet Gentong-Purwoasri SingosariMalang.In collecting these data the researchers used the method of observation,interviews, documentaries, questionnaires, and analyze the data inpercentages. Population taken in peneletian is the whole society Gentonghamlet of 200 people, while researchers only take 40 people (20%) tobe sampled comprised of community leaders, the village, the elderly andyouth.From the results of this study can be obtained from the data that thepurpose of the puppet Syadat is to disseminate the teachings of Islam and on the transformation of moral values of Islam through a puppet showSyadat dikatan be very effective. Because this approach is in accordancewith the background of village communities Gentong which largely favorthe arts that smelled gamelan.